Paediatric laryngeal squamous cell carcinoma: Systematic review and pooled analysis. (2nd February 2021) - Mur, Taha; Jaleel, Zaroug; Agarwal, Pratima; Edwards, Heather; Levi, Jessica R.
Abstract: Background: Paediatric squamous cell carcinoma (SCC) of the larynx is rare; however, recent data seem to support the notion that this pathology is increasing in incidence. Although this has been the case for several decades, treatment algorithms for this patient population remain identical to those of adults. Methods: The study consists of a systematic review and pooled analysis of oncologic outcomes in paediatric laryngeal SCC from a comprehensive literature search on OVID MEDLINE and EMBASE. Results: The average cohort age was 12.1 years. Nine (36%) had supraglottic primaries, and 16 (64%) had glottic primaries. Treatment included unimodal and combination therapy. No significant difference in survival was noted between surgically treated and non‐surgically treated patients (5‐year overall survival (OS): 68.2% vs 76.2%, P = .905), even when stratified for advanced‐stage and supraglottic disease. Conclusions: Paediatric patients with laryngeal HNSCC may have different presentations and responses to therapy than their adult counterparts.